Vascular plant biodiversity of Dorset and Mallik islands, Nunavut, Canada: an annotated checklist of a middle Arctic flora in the Canadian Arctic Archipelago - Saarela, Jeffery M.; Sokoloff, Paul C.; Bull, Roger D. (Phytotaxa, 2020)
Establishing a baseline of current Arctic vascular plant diversity and distribution is critical, given the rapid and major environmental changes occurring in the Arctic ecozone in response to climate change. Here, we report the results of a floristic study of vascular plant diversity of Dorset and Mallik islands in the Canadian Arctic Archipelago, Nunavut, Canada. These two small islands lie off the coast of the Foxe Peninsula of southwestern Baffin Island, and they are part of the Circumpolar Arctic bioclimate Subzone C. The hamlet of Kinngait (formerly Cape Dorset) is located on Dorset Island, and Nunavut’s Mallikjuak Territorial Park encompasses all of Mallik Island. The study is based on a specimen-based dataset comprising 876 unique collections from the two islands gathered over the last century, including 268 new ones collected in 2015. Results are presented in an annotated checklist. The vascular plant flora of the study area comprises 26 families, 71 genera, 150 species and three infraspecific taxa; 139 species are recorded on Dorset Island and 102 on Mallik Island. Eleven taxa are newly recorded from the study area in six families: Carex rupestris, Eriophorum scheuchzeri subsp. scheuchzeri, E. triste (Cyperaceae); Diapensia lapponica (Diapensiaceae); Equisetum arvense subsp. alpestre (Equisetaceae); Oxytropis deflexa var. foliolosa (Fabaceae); Potentilla arenosa subsp. arenosa, P. hyparctica subsp. hyparctica (Rosaceae); Antennaria friesiana subsp. friesiana, Askellia pygmaea, and Taraxacum phymatocarpum (Asteraceae).